If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7q + 2(3 + -2w) = 4(w + 2) + -1(w + -6) 7q + (3 * 2 + -2w * 2) = 4(w + 2) + -1(w + -6) 7q + (6 + -4w) = 4(w + 2) + -1(w + -6) Reorder the terms: 6 + 7q + -4w = 4(w + 2) + -1(w + -6) Reorder the terms: 6 + 7q + -4w = 4(2 + w) + -1(w + -6) 6 + 7q + -4w = (2 * 4 + w * 4) + -1(w + -6) 6 + 7q + -4w = (8 + 4w) + -1(w + -6) Reorder the terms: 6 + 7q + -4w = 8 + 4w + -1(-6 + w) 6 + 7q + -4w = 8 + 4w + (-6 * -1 + w * -1) 6 + 7q + -4w = 8 + 4w + (6 + -1w) Reorder the terms: 6 + 7q + -4w = 8 + 6 + 4w + -1w Combine like terms: 8 + 6 = 14 6 + 7q + -4w = 14 + 4w + -1w Combine like terms: 4w + -1w = 3w 6 + 7q + -4w = 14 + 3w Solving 6 + 7q + -4w = 14 + 3w Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + 7q + -6 + -4w = 14 + -6 + 3w Reorder the terms: 6 + -6 + 7q + -4w = 14 + -6 + 3w Combine like terms: 6 + -6 = 0 0 + 7q + -4w = 14 + -6 + 3w 7q + -4w = 14 + -6 + 3w Combine like terms: 14 + -6 = 8 7q + -4w = 8 + 3w Add '4w' to each side of the equation. 7q + -4w + 4w = 8 + 3w + 4w Combine like terms: -4w + 4w = 0 7q + 0 = 8 + 3w + 4w 7q = 8 + 3w + 4w Combine like terms: 3w + 4w = 7w 7q = 8 + 7w Divide each side by '7'. q = 1.142857143 + w Simplifying q = 1.142857143 + w
| 2(4-4)+32= | | 2y=3y-13 | | 5(y-2)-2=(y+1)-5 | | 97/5-x/5=2.6 | | 6a=a+5 | | 2.5x=-20 | | 12x+3=8x+43 | | 18u+3=10u | | -39=1-5(-7) | | 4x-5y-5=0 | | 14d=10d+12 | | 8x+y=177 | | 97-x/5=2.6 | | Y=-0.02x^2+.5 | | 6x+4.5y=50 | | 8x-6=5x-10 | | 10x×1/5 | | 3+3(a+2)= | | (3+3i)(2-3i)= | | 2.5x(2.5x)+3x=2 | | -7x-129=113+4x | | 2s=s+16 | | 5x(5x)+3x=2 | | 5x+2y-5z=16 | | X=ln(3x) | | 3(a+1)-5=3a-4 | | -s=x-5 | | -96-11x=2x+151 | | 4(x-5)=-25 | | xy^3/x^2y^2 | | -4x-41=28-7x | | 35(26)(0)= |